A novel Pseudomonas gessardii strain LZ-E simultaneously degrades naphthalene and reduces hexavalent chromium. (May 2016) - Huang, Haiying; Wu, Kejia; Khan, Aman; Jiang, Yiming; Ling, Zhenmin; Liu, Pu; Chen, Yong; Tao, Xuanyu; Li, Xiangkai
Highlights: Pseudomonas gessardii LZ-E degrades naphthalene and reduces Cr(VI) simultaneously. Naphthalene degradation promoted Cr(VI) reduction in strain LZ-E. Naphthalene degradation intermediates can reduce Cr(VI). Strain LZ-E was able to remediate naphthalene and Cr(VI) in an aerated bioreactor. Abstract: Combined pollutants with polycyclic aromatic hydrocarbons (PAHs) and heavy metals have been identified as toxic and unmanageable contaminates. In this work, Pseudomonas gessardii strain LZ-E isolated from wastewater discharge site of a petrochemical company degrades naphthalene and reduces Cr(VI) simultaneously. 95% of 10 mg L −1 Cr(VI) was reduced to Cr(III) while 77% of 800 mg L −1 naphthalene was degraded when strain LZ-E was incubated in BH medium for 48 h. Furthermore, naphthalene promotes Cr(VI) reduction in strain LZ-E as catechol and phthalic acid produced in naphthalene degradation are able to reduce Cr(VI) abiotically. An aerated bioreactor system was setup to test strain LZ-E's remediation ability. Strain LZ-E continuously remediated naphthalene and Cr(VI) at rates of 15 mg L −1 h −1 and 0.20 mg L −1 h −1 of 800 mg L −1 naphthalene and 10 mg L −1 Cr(VI) addition with eight batches in 16 days. In summary, strain LZ-E is a potential applicant for combined pollution remediation.